Magnetic resonance evaluation of three-dimensional liver fat fraction by hepatitis C status and associations with inflammatory cytokines. - Jessie Torgersen; Craig W Newcomb; Dean M Carbonari; Shanae M Smith; Katherine L Brecker; Chamith S Rajapakse; Brandon C Jones; Christiana Cottrell; Rasleen Grewal; Jennifer C Price; Joshua F Baker; Jay R Kostman; et al. (PLoS ONE, 2025)
Background Chronic hepatitis C virus (HCV) infection may influence cytokine and insulin-like growth factor (IGF-1) levels, which could contribute to increased hepatic steatosis. We utilized MRI to compare three-dimensional volumetric liver fat fraction by chronic HCV status and evaluated associations between liver fat fraction and inflammatory cytokines and IGF-1. Methods Participants with untreated, non-genotype 3 chronic HCV and participants without HCV were enrolled between 2019-2022 and underwent MRI to quantify three-dimensional volumetric liver fat fraction. Interleukin (IL)-6, IL-18, tumor necrosis factor (TNF)-α, and IGF-1 were also measured. Multivariable linear regression was used to determine associations between liver fat fraction, chronic HCV, and cytokine and IGF-1 levels. Results Among 54 participants with HCV and 54 without HCV, median volumetric liver fat fraction was 12.4% (IQR: 9.3, 18.0%) and 10.9% (IQR: 8.7, 13.3%), respectively. After adjustment for age, sex, and body mass index, mean liver fat fraction was 2.28% (95% CI: 0.55, 4.02%) higher in participants with HCV. HCV was associated with higher mean log TNF-α (0.11 [95% CI: 0.06, 0.16]) and IL-18 (0.14 [95% CI: 0.05, 0.24]), but lower mean log IGF-1 (-0.18 [95% CI: -0.26, -0.11]) when compared to those without HCV. IL-6, IL-18, TNF-α, and IGF-1 were not associated with liver fat fraction. Conclusion Chronic HCV is associated with higher volumetric liver fat fraction by MRI. TNF-α and IL-18 levels were higher with chronic HCV but were not associated with liver fat fraction. Further research is needed to identify alternative mechanisms that potentiate liver fat deposition in chronic HCV.